Profil Berpikir Kreatif Melalui Project Based Learning Bermuatan ESD pada Konsep Sel Siswa Kelas XI MIPA SMAN 1 Bantarbolang - Nur Hidayati; Joko Siswanto (Universitas PGRI Semarang, 2020)
Creative thinking is one of the 21st century skills. The development of creative thinking skills can be done using a learning model Project Based Learning (PjBL). The development of the model PjBL charged ESD (Education For Sustainable Development) aims to explore the potential of creativity and to instill awareness and concern for the environment for sustainable development. Research samples students of class XI MIPA SMAN 1 Bantarbolang. This research is a descriptive research with quantitative methods conducted by administering the test related creative thinking skills and attitudes of creativity of the students. The instrument tests the ability of creative thinking developed in the form of a description with the indicators of fluency, flexibility, originality and elaboration. Instruments creative attitude of students consists of multiple choice questions which includes the attitude indicator creative thinking skills students are curious, imaginative, and original in the expression of ideas, freely expressed opinions and see the issue from various angles. The results showed that the ability of creative thinking of students in the concept of the cell as much as 10% of students already have the ability to think creatively, while 83% of students have the ability of creative thinking are and 7% of students have the ability to think low. The results of the questionnaire showed 23% of students have an attitude of creative high, while the other is respectively as much as 53% of students have an attitude of creative medium and 23% of other students still have a low creative attitude.